Anti-inflammatory and antinociceptive activities of Solenostemon monostachyus aerial part extract in mice - Jude Fiom Okokon; Koofreh Davis; Lucky Legbosi Nwidu (Mashhad University of Medical Sciences, 2016)
Objective: Solenostemon monostachyus is used in traditional medicine for the treatment of various ailments such as ulcer, hypertension, pains and inflammatory diseases. Evaluation of anti-inflammatory and analgesic activities of S. monostachyus aerial parts was carried out to ascertain its uses in traditional medicine. Materials and Methods: The aerial parts of S. monostachyus was cold extracted by soaking the dried powdered material in ethanol. The aerial parts crude extract (75 -225 mg/kg) of  S. monostachyus was investigated for analgesic and anti-inflammatory activities using various experimental models; acetic acid, formalin and thermal- induced pains models for analgesic study and carrageenin, egg albumin and xylene - induced edema models for anti-inflammatory investigation. Results: The extract caused a significant (pConclusion: The anti-inflammatory and analgesic effects of this plant may in part be mediated through the chemical constituents of the plant and the results of the analgesic action suggest central and peripheral mechanisms. The findings of this work confirm the ethno medical use of this plant to treat inflammatory conditions.